A STUDY ON THE LEVEL OF COGNITIVE FACTORS, AFFECTIVE FACTORS AND WRITING PERFORMANCE OF STUDENTS IN PAPER 4 OF THE MALAYSIAN UNIVERSITY ENGLISH TEST IN MALAYSIA - Balasundaram Shanmugam; Chew Fong Peng; Ng Lee Luan, (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
The aim of this study is to analyse the level of cognitive (background knowledge, thinking maps use, critical thinking) factors, affective (writing self-efficacy, second language (L2) writing anxiety) factors and writing performance among students. This research adopts a quantitative approach through a survey methodology. The sample comprises 400 Malaysian University English Test (MUET) students from 26 schools in Penang, Malaysia. Data has been collected using six instruments: five questionnaires as well as one argumentative writing task. Descriptive statistics, including mean, percentage, frequency, and standard deviation, have been used to answer the research question. The outcomes indicate that the levels of background knowledge, writing self-efficacy, critical thinking, thinking maps use, and L2 writing anxiety are moderate. Because writing is an integral part of MUET, the outcomes of this study can serve as a springboard from which teachers can gain a deeper appreciation for background knowledge, writing self-efficacy, critical thinking, thinking maps use, and L2 writing anxiety. As a result, it may shed light on what teachers may do to assist these L2 writers in improving their background knowledge, writing self-efficacy, critical thinking, thinking maps use and overcoming their writing anxiety, which possesses a negative impact on their output.